Application of Bentonite as an Anti-Filtration Material in Hydraulic Engineering: A Case Study of the Tudakul Reservoir (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Filtration through reservoir dam is a vital issue affecting the sustainability of hydraulic structures and the efficiency of water distribution. This study offers a comprehensive analysis of filtration management methods, focusing on bentonite as a filtration control membrane. The results of the Tudakul reservoir dam study highlight the structural challenges of filtration through porous soils, with water losses posing a huge threat to sustainability. Laboratory and theoretical studies monitor the performance of bentonite, which, due to its special swelling properties, creates a dense gel barrier when in contact with water. This study compares bentonite with alternative solutions, including concrete liners, comparing key parameters such as cost, ease of installation, self-healing properties and environmental impact. The results indicate that bentonite is a cost-effective, sustainable and durable filtration control membrane with large capacity for programs in water-scarce regions.